An Extension of the Mittag-Leffler Function and Its Associated Properties. (22nd September 2020) - Rahman, Gauhar; Saboor, Abdus; Anjum, Zunaira; Nisar, Kottakkaran Sooppy; Abdeljawad, Thabet
Abstract : Inspired by certain fascinating ongoing extensions of the special functions such as an extension of the Pochhammer symbol and generalized hypergeometric function, we present a new extension of the generalized Mittag-Leffler (ML) function ε a, b ; p, v κ z 1 in terms of the generalized Pochhammer symbol. We then deliberately find certain various properties and integral transformations of the said function ε a, b ; p, v κ z 1 . Some particular cases and outcomes of the main results are also established.